Biomechanical indicators of key elements of sports equipment gymnastic exercises - Potop, V. A.; Grad, R.; Boloban, V. N. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim of this study is to analyze the biomechanical performance of the kinematic and dynamic structures of key elements of sports techniques of basic exercises performed gymnasts aged 12 - 14 years to the vaulting and on the bars of different heights, on the basis of the method of postural orientation movements. The study involved 11 gymnasts doing exercises on the vaulting and 9 gymnasts - on the boards of various heights. It is shown that the method of video - computer analysis of the type Yurchenko vault and dismount from the bars of varying heights, in conjunction with the method of postural orientation movements possible to isolate and identify the node elements. The indicators characterizing the node elements of sports equipment movements gymnasts in the phase structure of the vault and dismount from the bars of different heights have specific features and characteristics. Learned node elements sports equipment is the basis for the measurement, analysis and evaluation of the kinematic and dynamic structures and other types of exercises all-around gymnastics.